Dopamine D1 receptor activation regulates the expression of the estrogen synthesis gene aromatase B in radial glial cells - Xing, Lei; McDonald, Heather; Da Fonte, Dillon F.; Gutierrez-Villagomez, Juan M.; Trudeau, Vance (Frontiers in Neuroscience, 2015)
Radial glial cells (RGCs) are abundant stem-like non-neuronal progenitors that are important for adult neurogenesis and brain repair, yet little is known about their regulation by neurotransmitters. Here we provide evidence for neuronal-glial interactions via a novel role for dopamine to stimulate RGC function. Goldfish were chosen as the model organism due to the abundance of RGCs and regenerative abilities of the adult central nervous system. A close anatomical relationship was observed between tyrosine hydroxylase-positive catecholaminergic cell bodies and axons and dopamine-D1 receptor expressing RGCs along the ventricular surface of telencephalon, a site of active neurogenesis. A primary cell culture model was established and immunofluorescence analysis indicates that in vitro RGCs from female goldfish retain their major characteristics in vivo, including expression of glial fibrillary acidic protein and brain lipid binding protein. The estrogen synthesis enzyme aromatase B is exclusively found in RGCs, but this is lost as cells differentiate to neurons and other glial types in adult teleost brain. Pharmacological experiments using the cultured RGCs established that specific activation of dopamine D1 receptors up-regulates aromatase B mRNA through a cyclic adenosine monophosphate-dependent molecular mechanism. These data indicate that dopamine enhances the steroidogenic function of this neuronal progenitor cell.